تطبيق_وسائل_تعليم_العربية_الجزيرة_في_تعليم_المهارة - Salsabila, Luthfiya (Maliki Interdisciplinary Journal, 2024)
This research aims to describe the use of Aljazeera as a learning medium for teaching writing skills to students in the Arabic Language Education Department at Maulana Malik Ibrahim State Islamic University Malang. Aljazeera Education is a website featuring vocabulary, reading texts, images, and videos useful for learning Arabic. The study uses a qualitative descriptive methodology, including participant observation, interviews, and documentation. Data was collected from 18 students in the CK class of 2020 and a teacher from the Arabic Language Education Department. The findings reveal that Aljazeera Education helps students improve their writing skills by summarizing reading texts. The site offers several advantages: attractive images, easy access, and content tailored to various skill levels. However, it also has disadvantages; beginners may struggle to understand the Arabic content, and it is not suitable for students who still require teacher assistance.